3.7 Sand, report on the coarse pottery (Scottish Historical and Archaeological Internet Reports, 2009)
All of the sherds were small or abraded and had no diagnostic attributes. Fabric has yet to be proved a reliable indicator of date. Most of the pottery comes from high spits and topsoil contexts. As such it does not relate to the Mesolithic use of the site.